Bendamustine plus rituximab for indolent B‐cell lymphoma of renal significance. Issue 3 (6th December 2017) - Ribes, David; Hachem, Hélène E. L.; Oberic, Lucie; Vergez, François; Delas, Audrey; Belliere, Julie; Protin, Caroline; Kamar, Nassim; Ferrandiz, Inès; Tavitian, Suzanne; Laurent, Camille; Huart, Antoine; et al.
Abstract: Treatment of indolent B‐cell non‐Hodgkin lymphomas (iNHL) of renal significance is challenging given the need for deep and prolonged hematological response to restore and control renal function overtime, yet to be balanced with the risk of adverse drug‐related events. This prospective single‐center study included 20 patients with iNHL of renal significance (tubulointerstitial presentation [ n  = 8], glomerulopathy with or without monoclonal Ig deposits [ n  = 12]) who received a steroid‐sparing regimen of rituximab plus bendamustine (BR), with either no or <1 month of steroid intake (as a first line therapy in 80%). Seventeen patients (85%) achieved a complete (CHR, n  = 12) or a partial (PHR, n  = 5) hematological response. Nine out of the 12 patients (75%) with iNHL‐related glomerulopathy had a complete (CRR) or a partial (PRR) renal response. Among the six patients with glomerulopathy and CHR, five had a CRR (83%) compared to 1/6 (17%) that did not reach CHR. eGFR increased from 38 to 58 mL/min/1.73 m 2, and returned to baseline in five patients. Among the eight patients with a tubulointerstitial presentation, six (75%) had a renal response (5 CRR), and eGFR increased from 29 to 48 mL/min/1.73 m 2 . One patient with a PHR had a renal relapse. Mortality rate was 10% at 12 months. The BR regimen was well tolerated overall. Thus, despite severe renal disease at presentation, a relapsing iNHL in 20% of patients and several comorbidities, the BR regimen was efficient and safe in our series. It should be further assessed as a first line therapy for patients with iNHL of renal significance.